Caught in action: how MSCs modulate atherosclerotic plaque - Egea, Virginia (Frontiers in Cell and Developmental Biology, 2024)
Atherosclerosis (AS) is a medical condition marked by the stiffening and constriction of the arteries. This is caused by the accumulation of plaque, a substance made up of fat, cholesterol, calcium, and other elements present in the blood. Over time, this plaque solidifies and constricts the arteries, restricting the circulation of oxygen-rich blood to the organs and other body parts.The onset and progression of AS involve a continuous inflammatory response, including the infiltration of inflammatory cells, foam cells derived from monocytes/macrophages, and inflammatory cytokines and chemokines. Mesenchymal stromal cells (MSCs), a type of multipotent stem cells originating from various body tissues, have recently been demonstrated to have a protective and regulatory role in diseases involving inflammation. Consequently, the transplantation of MSCs is being proposed as a novel therapeutic strategy for atherosclerosis treatment. This mini-review intends to provide a summary of the regulatory effects of MSCs at the plaque site to lay the groundwork for therapeutic interventions.